Effect of land use systems on soil health in eastern region of Uttar Pradesh - DIWAKAR, SANDEEP KUMAR; ZAIDI, S F A; KUMAR, SURESH; KUMAR, AMIT; AVASTHE, R K; SINGH, RAGHAVENDRA; BABU, SUBHASH; GUDADE, B A; VERMA, GAURAV; KUMAR, NAVANEET (The Indian Journal of Agricultural Sciences, 2025)
Based on the findings of present investigation, it can be inferred that physico-chemical properties and microbial population in soil was also varied with land use whereas the physico-chemical properties and microbial population were generally improved in kharif as compared to rabi. Plantation land use was the best land use system followed by forest land use system for sustainable improvement of soil health may be recommended in the eastern region of Uttar Pradesh or similar agro ecoregions.